A Systematic Review of the Efficacy of Alcohol Interventions for Incarcerated People. (10th May 2018) - Newbury-Birch, Dorothy; Ferguson, Jennifer; Landale, Sarah; Giles, Emma L; McGeechan, Grant J; Gill, Charlotte; Stockdale, Kelly J; Holloway, Aisha
Abstract : Levels of risky drinking and dependency are high amongst incarcerated individuals. Eleven studies from nine articles were included in the systematic review. Six of the studies included brief intervention and three extended interventions. Interventions have the potential to positively impact on risky drinking. More studies are needed in this setting. Abstract: Aim: The aim of this current study was to systematically review the literature on brief alcohol interventions for incarcerated individuals to ascertain the efficacy or effectiveness in making changes to either consumption of alcohol or other social outcomes. Short summary: Levels of risky drinking and dependency are high amongst incarcerated individuals. Eleven studies from nine articles were included in the systematic review. Six of the studies included brief intervention and three extended interventions. Interventions have the potential to positively impact on risky drinking. More studies are needed in this setting. Introduction: It has been shown that around three times as many incarcerated individuals are risky drinkers and alcohol dependency is ten times higher than in the general population. Methods: Systematic review of randomised controlled trials or matched group trials of the efficacy of psychosocial alcohol interventions for incarcerated individuals: we searched seven databases, with no restrictions on language, year or location from inception through to August 2017. The Critical Appraisal Skills Programme tool was used to assess the quality of included studies. The Template for Intervention Description and Replication checklist was used to ascertain intervention descriptions. Results: Nine studies from 11 papers were included in the analysis. Six of the studies included brief interventions and three extended interventions. Every study used a different measure of alcohol consumption. Three of the studies that looked at brief interventions and all of the three extended intervention studies found significant reductions in relation to alcohol outcomes. Conclusions: Results show that interventions in the prison setting have the potential to positively impact on alcohol use; however, because of small numbers and the use of different outcome measures we could not conduct a meta-analysis or generalise findings. Future studies are needed to standardise approaches to ensure greater rigour and efficacy.